Significance of and Challenges in Regulating Endocrine Disruptors – How Regulators and Industry Can Conquer? - Dhiman, Sandeep K.; Dureja, Harish (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Endocrine disruptors (EDs) disrupt the standard operation of the endocrine systems, resulting in untoward effects. EDs have gained extensive consideration due to their severe adverse impacts on public and wildlife health. A variety of compounds from both natural and synthetic origin may cause endocrine disruptions. These may be found in industrial chemicals, persistent organic pollutants, and products of regular use including pharmaceuticals, medical equipment, implants, medical/surgical and dental devices, cosmetics, food products, other consumer goods, their packaging and processing materials. Apart from direct consumption or use, these chemicals may impact by entering our food chain or ecosystem. These chemicals act by mimicking the hormones or blocking their receptors or interfering in their normal production, absorption, distribution, metabolism and excretion. The implementation of a regulatory framework on the complex multidisciplinary field of EDs brings enormous challenges, which pose barriers to the regulatory process. This study aims to focus on the key public and ecological health concerns presented by EDs, challenges faced by regulators to achieve successful regulatory proposition and the importance of collaboration endeavours to potentially conquer such challenges. Endocrine-disrupting chemicals (EDCs) or EDs can impact at low exposure levels, bringing about a broad range of health issues including disorders related to reproductive, fetal development, neurological, immunological, metabolic and cancer, etc. They may cause health effects across generations. The regulatory frameworks available across major regulators are tackling the identification of EDs and their mechanisms to provide necessary guidance on the safety and disposal of such substances. However, the challenges faced outweigh the regulatory mechanisms in place. The major challenges are related to structural ranges at times leading to no representative structures, active metabolites, substantiate quantum, delayed effects, epigenetic changes, widespread existence, concentration correlation for different biological species, availability of appropriate methods, exposure to a mixture of chemicals, complex endocrinology principles, unknown sources, routes and mechanisms, impacts at early stages of life, geographical movement of EDs, hazard-based vs. risk-based approaches. Regulators of healthcare and environmentalists needs to collaborate amongst them and with wider stakeholders including industry sponsors to find ways of dealing with such challenges and capitalize on the research-based knowledge grid available across institutions. Existence of EDs, their impact on living beings and mechanism of influence are like a tangled web, which induces difficulties in regulating them with conventional mindset. Conquering these challenges necessitates that regulators should join forces amongst themselves, with other institutions operating for environment, with industry sponsors and researchers to achieve success in public health safety.
Keywords: EDCs